WANITA DALAM SERAT NITIPRAJA - Arsanti Wulandari (Humaniora, 2006)
Serat Nitipraja (SNP) is a text which is contain a guiding for leader. The leader must have religius and humanity characters. In SNP we can read about the person who stand next to leader like ulama, ambassador and woman. The special thing is there is a woman subject in the text which is talk about leader. It is interesting because in the Javanese culture, woman does not have any chance to talk in public area, but in text woman can do it. As a render assistance for leader, woman can play in the leader area with her womanhood to have a chance to make a decission in public sector.